Social Entrepreneurship as a Form of Gen Z Social Awareness in the Digital Era - Muhammad Alfa Sikar; Nur Ilmiah Rivai; Agus (Association Of Indonesian Entrepreneurship Study Programs, 2024)
Social Entrepreneurship as a Form of Social Awareness of Gen Z in the Digital Era The dominance of the young generation population in the digital era for a country can be both positive and negative. A social entrepreneur is an individual who leads positive change in society in an innovative, creative, and sustainable way. They not only focus on financial gain, but also aim to solve significant social or environmental problems. The literature study method where this research is carried out is only based on written works, including the results of research both published and unpublished. This conclusion confirms that collaboration between Gen Z as social entrepreneurs with non-profit organizations and the government not only expands the reach and strengthens the support base, but also produces more holistic and sustainable solutions in addressing social problems. Through this collaboration, they can combine their expertise and resources to face larger and more complex challenges, creating a deeper and more sustainable impact in society.